1997
DOI: 10.1161/01.atv.17.4.741
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Variation in Patients Heterozygous for Familial Defective Apolipoprotein B (FDB) in Three European Countries

Abstract: A glutamine-for-arginine substitution at amino acid position 3500 of apolipoprotein B (apo B) causes synthesis of LDL with reduced binding affinity to the LDL receptor (LDLR). The associated clinical syndrome has been named familial defective apolipoprotein B- 100 (FDB). In 205 FDB patients from Germany (n = 73). The Netherlands (n = 87), and Denmark (n = 45), we tried to assess determinants of variation in lipid concentrations. Besides age, sex, and geographic origin, variation in the LDLR gene was the most p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 30 publications
1
21
1
Order By: Relevance
“…It has emerged that some people with familial liganddefective apoB100 due to R3500 and R3531 mutations have plasma cholesterol levels within the normal range (302)(303)(304)(305)(306), despite defective LDL binding and accumulation of the mutant allotype in blood. In one study, Pullinger et al ( 304 ) showed by using a monoclonal antibody and dynamic light scattering that the mass ratio of Gln3500 to Arg 3500 in the LDL of heterozygote apoB100 R3500Q patients was ‫ف‬ 73:27 and that in vitro the mutant LDL had <10% of the normal affi nity for the LDLR.…”
Section: Apob Mutations Defective Ldlr Binding and Adh-2mentioning
confidence: 99%
“…It has emerged that some people with familial liganddefective apoB100 due to R3500 and R3531 mutations have plasma cholesterol levels within the normal range (302)(303)(304)(305)(306), despite defective LDL binding and accumulation of the mutant allotype in blood. In one study, Pullinger et al ( 304 ) showed by using a monoclonal antibody and dynamic light scattering that the mass ratio of Gln3500 to Arg 3500 in the LDL of heterozygote apoB100 R3500Q patients was ‫ف‬ 73:27 and that in vitro the mutant LDL had <10% of the normal affi nity for the LDLR.…”
Section: Apob Mutations Defective Ldlr Binding and Adh-2mentioning
confidence: 99%
“…2 There is some evidence that LDL cholesterol levels show some variation among affected persons in FH and FDB families. [3][4][5] However, one is usually not able to distinguish clinically between FH and FDB, 6 although there may be a trend toward lower LDL cholesterol levels in FDB patients. 4 There are Ͼ600 mutations described for the LDL receptor.…”
mentioning
confidence: 99%
“…[3][4][5] However, one is usually not able to distinguish clinically between FH and FDB, 6 although there may be a trend toward lower LDL cholesterol levels in FDB patients. 4 There are Ͼ600 mutations described for the LDL receptor. 7 Despite this large number, mutations have not been identified in up to 30% of all persons with FH.…”
mentioning
confidence: 99%
“…In the apoB gene, the arginine 3500 to glutamine mutation is also common and affects about one in 600 people. 2 This mutation seems to be of central European origin and could not be identified in other Europeans, such as Finns and Russian.…”
mentioning
confidence: 91%